2020
DOI: 10.1177/0361198119896782
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting the Quality of Service of Bogota’s Sidewalks from Pedestrian Perceptions: An Ordered Probit MIMIC Approach

Abstract: A variety of different pedestrian performance or service indicators (PPSI), such as the pedestrian level of service (PLOS), or quality of service (QoS), have been developed to evaluate pedestrian infrastructure. Although modeling approaches vary (e.g., ordinal least squares, scoring system), the great majority use on-site measurable attributes, such as sidewalk width or adjacent traffic, to estimate the PPSI. However, most of these models have been developed without jointly considering objective and subjective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 43 publications
2
11
0
1
Order By: Relevance
“…Among the variables included in the model, the environment can be considered as the most important aspect for young pedestrians. This result is also amply confirmed by other studies in the literature [26,27]. In particular, "environment" is one of the most relevant attributes, especially when its definition also includes the concept of security [28].…”
Section: Discussionsupporting
confidence: 78%
“…Among the variables included in the model, the environment can be considered as the most important aspect for young pedestrians. This result is also amply confirmed by other studies in the literature [26,27]. In particular, "environment" is one of the most relevant attributes, especially when its definition also includes the concept of security [28].…”
Section: Discussionsupporting
confidence: 78%
“…If the goal of sidewalk design would be less normative (attaining standards) and it shifts to creating approachable and attractive sidewalks, using walker perceptions to relate to QoS (or other target variables such as satisfaction or comfort) would be indispensable. In relation to developing QoS evaluation or forecasting models using perceptions, advanced techniques such as Multiple Indicators Multiple Causes (MIMIC) such as the one applied by Vallejo-Borda et al can be the path to be followed ( 50 ). In both cases, this paper raises an interesting discussion on the general approach and philosophy of complete streets manuals.…”
Section: Discussionmentioning
confidence: 99%
“…In an attempt to fill this gap, Fernández-Heredia et al suggested that including user perceptions to mode choice models could improve their performance ( 49 ). Furthermore, Vallejo-Borda et al proposed a model that contemplates these environmental stimuli to forecast the pedestrian QoS ( 50 ). However, it is not common to find models that include perceptions to estimate QoS in the literature.…”
Section: Literature Reviewmentioning
confidence: 99%
“…From a larger perspective, results presented herein constitute a building block to the planning of urban renewal interventions. The latter, in synchrony with other urban structures analyses (e.g., trees, highways, cycling paths, or sidewalks [Rodriguez‐Valencia, Barrero, Ortiz‐Ramirez, & Vallejo‐Borda, 2020; Vallejo‐Borda, Cantillo, & Rodriguez‐Valencia, 2020]), represent an opportunity for urban renewal, while decreasing the risk of failure and improving the perception of sewer system quality of service (Vallejo‐Borda, Ortiz‐Ramirez, Rodriguez‐Valencia, Hurtubia, & de D. Ortúzar, 2020).…”
Section: Discussionmentioning
confidence: 99%